Early Stent Thrombosis and Mortality After Primary Percutaneous Coronary Intervention in ST-Segment–Elevation Myocardial Infarction: A Patient-Level Analysis of 2 Randomized Trials. (May 2016) - Dangas, George D.; Schoos, Mikkel M.; Steg, Philippe Gabriel; Mehran, Roxana; Clemmensen, Peter; van 't Hof, Arnoud; Prats, Jayne; Bernstein, Debra; Deliargyris, Efthymios N.; Stone, Gregg W.
Abstract : Background—: Early stent thrombosis (ST) within 30 days after primary percutaneous coronary intervention in ST-segment–elevation myocardial infarction is a serious event. We sought to determine the predictors of and risk of mortality after early ST according to procedural antithrombotic therapy. Methods and Results—: In a patient-level pooled analysis from the Harmonizing Outcomes With Revascularization and Stents in Acute Myocardial Infarction (HORIZONS-AMI) and European Ambulance Acute Coronary Syndrome Angiography (EUROMAX) trials, we examined 30-day outcomes in 4935 patients undergoing primary percutaneous coronary intervention with stent implantation at 188 international sites, randomized to either bivalirudin or heparin±a glycoprotein IIb/IIIa inhibitor (GPI). Early ST occurred in 100 patients (2.0%), 20 of whom (20.0%) died. Bivalirudin was associated with higher rates of early ST compared with heparin±GPI (2.5% versus 1.6%, P =0.04), because of more acute (⩽24 h) ST (1.5% versus 0.2%, P <0.0001), with the risk limited to the first 4 hours after percutaneous coronary intervention. The rates of subacute (1–30 days) ST were similar with bivalirudin and heparin±GPI (1.0% versus 1.4%, P =0.24). Among patients with early ST, mortality within 30 days occurred in 4 of 60 (6.7%) bivalirudin-treated patients compared with 16 of 40 (40.0%) heparin±GPI–treated patients (adjusted hazard ratio, 0.12; 95% CI, 0.04–0.39; P =0.0004 and adjusted hazard ratio, 0.122; 95% CI, 0.04–0.39; P =0. 0004). Thus, 30-day mortality attributable to early ST occurred in 4 of 2479 (0.2%) bivalirudin-treated patients versus 16 of 2456 (0.7%) heparin±GPI–treated patients ( P =0.007). Conclusions—: In the present large-scale pooled analysis from 2 multicenter randomized trials, early ST was more frequent in patients treated with bivalirudin compared with heparin±GPI because of increased ST within 4 hours after primary percutaneous coronary intervention. However, the mortality attributable to early ST was significantly lower after bivalirudin than after heparin±GPI. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifiers: NCT00433966 (HORIZONS-AMI) and NCT01087723 (EUROMAX). Abstract : Supplemental Digital Content is available in the text.